Neurochemistry of Enteric Neurons Following Prolonged Indomethacin Administration in the Porcine Duodenum - Czajkowska, Marta; Całka, Jarosław (Frontiers in Pharmacology, 2020)
Gastrointestinal inflammation resulting from prolonged NSAID drugs treatment constitutes a worldwide medical problem. The role of enteric neuroactive substances involved in this process has recently gained attention and neuropeptides produced by the enteric nervous system may play an important role in the modulation of gastrointestinal inflammation. Therefore, the aim of this study was to determine the effect of inflammation caused by indomethacin supplementation on vasoactive intestinal polypeptide (VIP), substance P (SP), neuronal nitric oxide synthase (nNOS), galanin (GAL), pituitary adenylate cyclase-activating polypeptide (PACAP) and cocaine- and amphetamine-regulated transcript peptide (CART) expression in enteric duodenal neurons in domestic pigs. Eight immature pigs of the Pietrain x Duroc race (20 kg of body weight) were used. Control animals (n=4) received empty gelatine capsules. Experimental pigs (n=4) were given indomethacin for 4 weeks, orally 10 mg/kg daily, approximately 1 h before feeding. The animals from both groups were then euthanized. Frozen sections were prepared from the collected duodenum and subjected to double immunofluorescence staining. Primary antibodies against neuronal marker PGP 9.5 and VIP, nNOS, SP, GAL, CART and PACAP were visualized with Alexa Fluor 488 and 546. Sections were analyzed under an Olympus BX51 fluorescence microscope. Microscopic analysis showed significant increases in the number of nNOS-, VIP-, SP-, GAL-, PACAP- and CART-immunoreactive ganglionic neurons, in both the myenteric and submucous plexuses of the porcine duodenum. The obtained results show the participation of enteric neurotransmitters in the neuronal duodenal response to indomethacin-induced inflammation.